Teaching Experiments: A Classroom Primer - Haupert, Michael J.; Netusil, Noelwah R. (My University, 1999)
The article focuses on a classroom primer for teachers who are interested in using experimentation as an educational aid. It is noted that incorporating experiments into the classroom improves student involvement with the material, develops interpersonal communication skills, sharpens critical thinking, and offers an alternative to standard lecture. Most experiments are flexible and can be tailored to reflect different course levels and instructor needs and preferences. The preparation of two experiments for the first semester is recommended.
Keywords: education -- experimental methods, education -- research, interpersonal communication, communication -- Study & teaching, critical thinking, business education, students, learning, teaching